Aualysis of ground strata control of mining in the era of big data - MA Zhanyuan, LI Huamin, LIU Chuang, WANG Shen (Meikuang Anquan, 2021)
In recent years, with the gradual development of information technology, mine big data and mine intelligent mining technology have been developed rapidly. In the aspect of mine intelligent rock control, due to the various types of data related to it, it is difficult to integrate, the problems involved are complex, and the intelligent path is not clear enough, which leads to the research and application of mine big data and mine intelligent rock control technology progress has been slow. Combined with the characteristics of mining engineering, this paper analyzes the characteristics of mine big data and intelligent strata control in mining, discusses the key scientific problems and main research contents of intelligent strata control in mining, establishes a numerical simulation system of intelligent strata control based on mine big data platform and dynamic inversion, and studies its key technology and implementation path.